2021
DOI: 10.1101/2021.03.02.433611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compositional analysis of ALS-linked stress granule-like structures reveals factors and cellular pathways dysregulated by mutant FUS under stress

Abstract: Formation of cytoplasmic RNA-protein structures called stress granules (SGs) is a highly conserved cellular response to stress. Abnormal metabolism of SGs may contribute to the pathogenesis of (neuro)degenerative diseases such as amyotrophic lateral sclerosis (ALS). Many SG proteins are affected by mutations causative of these conditions, including fused in sarcoma (FUS). Mutant FUS variants have high affinity to SGs and also spontaneously form de novo cytoplasmic RNA granules. Mutant FUS-containing assemblies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…However, the similar protein population detected does not exclude that FUS P525L could affect SG proteome arrangement. In fact, using published datasets of known FUS protein interactors (42,(44)(45)(46)(47), we found a consistent overlap with already identified SG components. Noteworthy, we observed that some of these FUS protein interactors are more engaged into SG, and their RNA binding ability could contribute to the described transcriptome alterations.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, the similar protein population detected does not exclude that FUS P525L could affect SG proteome arrangement. In fact, using published datasets of known FUS protein interactors (42,(44)(45)(46)(47), we found a consistent overlap with already identified SG components. Noteworthy, we observed that some of these FUS protein interactors are more engaged into SG, and their RNA binding ability could contribute to the described transcriptome alterations.…”
Section: Discussionsupporting
confidence: 79%
“…Noteworthy, we observed that some of these FUS protein interactors are more engaged into SG, and their RNA binding ability could contribute to the described transcriptome alterations. Furthermore, we also observed that the FUS-interacting protein components of SG exhibit a significantly higher potential to form protein-protein physical interactions; this characteristic has been previously documented for the aggregated state of FUS R522G interactors (42). Moreover, the physical interactions considered for this analysis include those involved in the formation of protein complexes (STRING database) and extend beyond contacts simply involving the low-complexity domains (LCDs) of proteins.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations